HUBUNGAN KARAKTERISTIK PETANI DAN PERILAKU KOMUNIKASI PETANI DALAM PEMENUHAN INFORMASI USAHATANI LADA DI DESA SUKADANA BARU, KECAMATAN MARGA TIGA, KABUPATEN LAMPUNG TIMUR - Kiki Ambarwati; Indah Nurmayasari; Rio Tedi Prayitno (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purposes of this study are to determine the communication behavior of pepper farmers, characteristics of pepper farmers and analyze the correlation between farmers’ characteristics and communication behavior in fulfilling pepper farming information. This research was conducted in Sukadana Baru Village, Marga Tiga District, East Lampung regency in August 2018. This location was chosen purposively with consideration that Sukadana Baru Village is a village with the largest area and pepper production in East Lampung. The number of samples in this study were 43 pepper farmers. This study used a survey method, and data were analyzed using descriptive analysis and rank Spearman test. The results showed that all respondent farmers were at the productive age level with an average age of 42 years, average level of basic education of 9 years, the average cultivated area of 2.00 hectares, pepper farming experience 22 years, and the average monthly income of Rp2,591,382.00. Communication behavior of farmers in fulfilling pepper farming information fell into the medium category. There was a significant correlation between farmer's age, land size, and income with communication behavior in fulfilling pepper farming information.Key words: communication behavior,farmer characteristics, pepper